Capelas de Vila Rica: a vida festiva e os adros da freguesia de Antônio Dias do século XVIII a meados do XIX - Ingrid Aparecida Rogério Ribeiro (2020)
In order to rescue the important space of the churchyard from the 18th and 19th centuries's Chapels, and contribute to overcoming this verified gap in the research on Baroque religious temples, this work aims to highlight potential of these spaces in the eighteen-century Minas Gerais. Proposing a new look at religious monuments, the churchyard will be seen in the light of social relations that can be seen as a portrait of eighteenth-century religiosity and as an important architectural resource to enhance the religious monument. The research is structured in three chapters. To this end, the first chapter entitled Origins and structuring of the Christian Temple in Brazil will contextualize the regulatory aspects of the Church and the characteristics of the first buildings of sacred architecture erected in the Portuguese-Brazilian territory, presenting the strong Tridentine influence in the colony. The second chapter called The expression of religion in the eighteenth-century chapels in Vila Rica addresses the hierarchical relationship between the Portuguese Crown, Church and the Portuguese-Brazilian colony to understand decisive factors for adopting Catholic religious practices in Vila Rica and the consequent organization of the Church in the eighteenth-century Minas Gerais. We will also deal with the religious festivities experienced in Vila Rica and the devotions present in the suburban and urban chapels. Finally, the third chapter called The churchyards in the formation of religious architecture in eighteen-century Minas Gerais: the case of Vila Rica, to identify and discuss the role of churchyard in the formation of urban space – as intermediate publicprivate space. The announcements are categorized in typologies of Chapels and analyzed according to the perception of built environment and urban landscape. Thus, the churchyard will be examined as an architectural resource of significant urban articulation, enhancement of built monument, and space for sacred and profane relations in religious temples.